2011
DOI: 10.1029/2010ja016310
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sawtooth events and magnetic storms

Abstract: [1] The relationship between sawtooth events and magnetospheric substorms has been discussed extensively. However, the relationship between sawtooth events and magnetic storms has not been systematically examined. Using the sawtooth event list and magnetic storm list from January 1998 to December 2007, we investigate whether sawtooth events are storm time phenomena and whether there is a dependence on the strength and phase of storms. We have found that most of sawtooth events occur during storm time. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(66 citation statements)
references
References 40 publications
(57 reference statements)
2
63
1
Order By: Relevance
“…They found that storms tend to be stronger in August only if the IMF is antiparallel (away) with the Earth's. As most of sawtooth events were accompanied with intense storms [ Cai et al , ], our results agree with their conclusions. However, Oh and Yi [] only examined two solar minimums during which the background solar magnetic field could be considered as a dipole.…”
Section: Discussionsupporting
confidence: 93%
“…They found that storms tend to be stronger in August only if the IMF is antiparallel (away) with the Earth's. As most of sawtooth events were accompanied with intense storms [ Cai et al , ], our results agree with their conclusions. However, Oh and Yi [] only examined two solar minimums during which the background solar magnetic field could be considered as a dipole.…”
Section: Discussionsupporting
confidence: 93%
“…Observations show that ∼94 % of sawtooth events occur during geomagnetic storm times (Cai et al 2011). It is also known that the O + concentration inside the magnetosphere is highly correlated with geomagnetic storms.…”
Section: Sawtooth Eventsmentioning
confidence: 99%
“…The study by Cai et al . [] identified four STEs during this storm. Their criteria for designating events as STEs demanded repeated and nearly simultaneous observations of increased 50–450 keV proton fluxes by LANL satellites within ±3 h of local midnight and noon.…”
Section: Introductionmentioning
confidence: 95%
“…One storm time response, in the form of the SYM‐H index [ Iyemori , ], is shown in the bottom panel. The four vertical red lines superposed on the SYM‐H trace mark the times of the four identified STE onsets [ Cai et al ., ]. An examination of these data identifies four empirical results.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation